Analysis of the Eid Al-Fitr Holiday Anomaly on Abnormal Return and Trading Volume Activity: Case Study of Jakarta Islamic Index During 2017-2020 - Firman Pribadi; Aldi Abilawa (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This research aims to determine whether there is a significant difference in the average abnormal return on the Jakarta Islamic Index on the Indonesia Stock Exchange in 2017-2020 before and after the Eid al-Fitr holiday and find out whether there is a significant difference in the average trading volume activity on the Jakarta Islamic Index on the Indonesia Stock Exchange in 2017-2020 before and after the Eid al-Fitr holiday.Design/Methodology/Approach: By utilizing an event study, the only significant difference was in the Average Trading Volume Activity (ATVA), showing that trading activity before the holiday was higher, and the opposite occurred in the 2020 period.Research findings: The first research result is that investors could not earn any abnormal return on post- and pre-event windows since the differences between post- and pre-average abnormal returns were insignificant. The second result is a significant Eid al-Fitr anomaly through trading volume activity patterns in companies listed on the Jakarta Islamic Index on the Indonesia Stock Exchange. The results also indicate that the capital market in Indonesia is efficient in a semi-strong form of event in the pandemic era.Theoretical contribution/Originality: The anomalies in the market prove that the market is not always efficient, and it defies the Efficient Market Hypothesis (EMH). These anomalies have addressed non-economic factors, such as religion or culture. As one of the anomalies in the market, this study on holiday had mixed results. In addition, the Jakarta Islamic Index was used since the event studied in this research was the Islamic holiday, and Indonesia has the largest Muslim population in the world.Practitioner/Policy implication: This study is expected to be a reference material and information for companies about how investors respond to the Ramadan effect.Research limitation/Implication: Regarding the sample, this study was still limited to companies listed in the Jakarta Islamic Index, which only consists of 30 companies, so it is advisable to use companies listed on the Indonesian Sharia Stock Index.